Effects of kiai on jumping performance and striking reaction time in Karate athletes - Rodrigues, J. C. C.; Penna, E. M.; de Azevedo, A. B. C.; Meninea, D. S.; Magno, A. P.; Sant'Ana, J.; Coswig, V. S. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2022)
Background. Kiai is a breathing technique, usually related to a short scream that aims to focus the martial artist`s energy in a given attack. However, the influence of kiai in the technical and physical aspects related to striking performance needs more evidence. Thus, the purpose of this study was to investigate the effect of kiai in the performance of vertical jumps, and reaction time (RT) for punches and kicks in amateur Karate athletes. Methods. Sixteen male amateur athletes aged 18.5 ± 4.3, body mass of 68.5 ± 10 kg, height of 1.7 ± 0.1 m, and 2.4±1.8 years experience in Karate were recruited. Five attempts at each technical action and three attempts at each vertical jump were performed with and without using kiai. The RT was measured by the TReaction® app and the vertical jumps by using a contact mat. Paired t-tests and Cohen`s d effect sizes were used to test differences between conditions, while ANOVA was applied to test differences between attempts for both RT and jumps. Results. No significant differences were found between kiai and control conditions for the countermovement jump (CMJ; p= 0.496), squat jump (SJ; p= 0.374), and drop jump (DJ; p= 0.147) performance. There was no evidence (p> 0.05) of significant differences between conditions for punch and kick Rts. Conclusion. The kiai technique does not promote or affect RT of punch, kick, and vertical jump performance in Karate athletes.